MUHASABAH ‘ALA AL-NAFSI DITENGAH PANDEMI CORONA - Tarpin Tarpin (Sahaja: Journal Sharia and Humanities, 2022)
This article discusses about Muhasabah ‘ala nafsi (MAN) which is an attempt by a Muslim to decorate himself with pious deeds as well as to calculate, and evaluate themselves, how many bad deeds he has done and what good deeds he has not done. Whereas in Sufi terms, Muhasabah ‘ala nafsi means continuous analysis of the heart and its ever-changing circumstances. Apart from being meant by the term calculation, muhasabah 'ala nafs is also identified with the term self-calculation, self-evaluation, self-examination, introspection, self-attention or introspective, i'tishom and istiqomah for actions, attitudes, weaknesses, and errors related to oneself . Associated with the co-19 pandemic outbreak, the muhasabah ‘ala nafsi (MAN) as an afterthought for testing from Allah SWT, reminds us that we can be closer to Allah SWT. So that we can behave fairly in worshiping Allah SWT, as well as the worship of hablum minannas, hablum minal'alam namely to socialize well with fellow humans, and the natural environment.